Numerical Modeling and Mechanical Analysis of Combined Connection with Bolts and Welds - Liu, M.S; Li, C.A.; Huang, J.R.; Ju, J.S. (Проблемы прочности, 2016)
In this paper, a detailed finite element model of the combined connection with bolts and welds is created to analyze its failure mode and bearing capacity under shear load. The evaluation of work-together behavior of bolts and welds are focused on. С помощью программного комплекса ABAQUS выполнено конечноэлементное моделирование комбинированных болтовых и сварных соединений с целью изучения механизмов разрушения и несущей способности. Проанализирован вклад сварных швов и болтовых соединений в общую несущую способность конструкции. За допомогою програмного комплексу ABAQUS проведено скінченноелементне моделювання комбінованих болтових і зварних з єднань із метою вивчення механізмів руйнування і несівної здатності. Проаналізовано внесок зварних швів і болтових з єднань у загальну несівну здатність конструкції.